2005
DOI: 10.1111/j.1365-2486.2005.00991.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of changing CO2, temperature, precipitation, and ozone on carbon and water cycles of an upland‐oak forest: incorporating experimental results into model simulations

Abstract: Observed responses of upland-oak vegetation of the eastern deciduous hardwood forest to changing CO 2 , temperature, precipitation and tropospheric ozone (O 3 ) were derived from field studies and interpreted with a stand-level model for an 11-year range of environmental variation upon which scenarios of future environmental change were imposed. Scenarios for the year 2100 included elevated [CO 2 ] and [O 3 ] ( 1 385 ppm and 1 20 ppb, respectively), warming ( 1 4 1C), and increased winter precipitation ( 1 20%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 137 publications
(190 reference statements)
3
68
0
Order By: Relevance
“…The majority of the grass biomass in watershed 1D at Konza is produced by a few C 4 grass species (44); future research would need to compare the physiology of a range of grass species with different evolutionary histories to test this possibility. Likewise, although other studies have quantified the seasonal sensitivity of aspects of plant productivity to precipitation (14,15,45), more research in other sites will be necessary to understand the geographic patterns of seasonal sensitivity to climate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the grass biomass in watershed 1D at Konza is produced by a few C 4 grass species (44); future research would need to compare the physiology of a range of grass species with different evolutionary histories to test this possibility. Likewise, although other studies have quantified the seasonal sensitivity of aspects of plant productivity to precipitation (14,15,45), more research in other sites will be necessary to understand the geographic patterns of seasonal sensitivity to climate.…”
Section: Resultsmentioning
confidence: 99%
“…However, most climate variability would not be considered extreme and occurs on much shorter time scales throughout the growing season with temperature and precipitation frequently disassociated. The response of ecosystems to short-term climate variability at different times of year is thought to vary (11)(12)(13)(14)(15)(16)), but we know little about how the timing of short-duration climate variability impacts key ecosystem dynamics such as plant productivity.…”
mentioning
confidence: 99%
“…respiration and photosynthesis) influencing plant growth are also temperature sensitive, but differentially so, both among species and plant functional groups (Tjoelker et al, 1999;Hanson et al, 2005;Rennenberg et al, 2006;Wang et al, 2012). Net photosynthesis (primary production) typically peaks within the range of normally experienced temperatures (Kirschbaum, 2000;Berggren et al, 2009), which as described in the following section, is a key difference with respect to insect herbivores.…”
Section: Direct and Herbivore-mediated Climate Change Effects On Plantsmentioning
confidence: 99%
“…Controlled experiments and long-term observations can be helpful for understanding the responses of plants to global change. A 14-year controlled multifactor experiment was carried out in a temperate deciduous forest in the eastern part of the U.S. state of Tennessee (Hanson et al 2005). These authors found that a change in precipitation considerably influenced the physiological adjustments of trees and resulted in a change in leaf biomass.…”
Section: The Effect Of Climate On Nppmentioning
confidence: 99%